PENGARUH EFIKASI DIRI TERHADAP MINAT BERWIRAUSAHA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TEKNOLOGI SUMBAWA - Agus Syamsudin; Lukmanul Hakim; Ayuning Atmasari (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2019)
Unemployment is a complex problems faced by many people including undergraduate students. However, enterpreneurship interest becomes an alternative method to increase student self efficacy. The aim of this study is to understand effect of self confidence in enterpreneursip interest undergraduate students in Economic and Business of Faculty, Sumbawa University of Technology. This study using descriptive quantitative approach and the instrument using a questionnaire method. Instrument testing using validity “Product momen person” and reability test. Analysis data using simple linear regression and the number of responden is 90 students with spesific criteria. Analysis output showing that level of significant linear regression to enterpreneurship interest is 0,000 or smaller than 0,05, self-confidence give positive effect in enterpreneurship interest with regression cofficient value is 0,522. R Square output value is 0,377 showing that selfe-efficacy contribute as much 37,7% to made variable of enterpreneurship interest and the rest is formed outside the variable. Therefore, stated hypothesis is accepted showing that Self-confidence give effect to enterpreneurship interest undergraduate students in Economic and Business of Faculty, Sumbawa University of Technology. Based on the result of this study, it can be suggested that students should have strong self-efficacy and always increase their knowledge concern enterpereneurship to increase entereneurship interest and apply enterpreurial activies consistently.